2012
DOI: 10.1055/s-0032-1321506
|View full text |Cite
|
Sign up to set email alerts
|

New Dried Human Amniotic Membrane Is Useful as a Substitute for Dural Repair after Skull Base Surgery

Abstract: Objectives?Cerebrospinal fluid (CSF) leakage is an undesirable complication of skull base surgery. We used dried human amniotic membrane (AM) as a patch graft for dural repair to determine its efficacy in preventing CSF leakage. Design?Frontoparietal craniotomy and removal of dura were performed in 20 Wistar rats. A dried AM was placed to cover the dural defect without suturing in 16 animals. In four animals, an expanded polytetrafluoroethylene was implanted. At 2 weeks and 1, 3, and 6 months, histological ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
59
0
2

Year Published

2013
2013
2019
2019

Publication Types

Select...
5

Relationship

3
2

Authors

Journals

citations
Cited by 49 publications
(62 citation statements)
references
References 35 publications
1
59
0
2
Order By: Relevance
“…The AM was then air dried and sterilized by gamma irradiation at 25 kGy, which has been recommended for terminal sterilization of medical products 19. These procedures can completely prevent already‐known transmissible infections, and no adverse effects have been reported in patients receiving hyperdry AM grafts 10, 20. To manage unexpected risks, however, it is essential to accurately record in the recipient's case notes all unique donation numbers of all grafts used, to store samples corresponding to each donation number, and to undertake long‐term monitoring of the recipients after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…The AM was then air dried and sterilized by gamma irradiation at 25 kGy, which has been recommended for terminal sterilization of medical products 19. These procedures can completely prevent already‐known transmissible infections, and no adverse effects have been reported in patients receiving hyperdry AM grafts 10, 20. To manage unexpected risks, however, it is essential to accurately record in the recipient's case notes all unique donation numbers of all grafts used, to store samples corresponding to each donation number, and to undertake long‐term monitoring of the recipients after the operation.…”
Section: Discussionmentioning
confidence: 99%
“…The hyperdry device and sterilization by γ‐irradiation at 25 kGy, which has been recommended for terminal sterilization of medical products, can completely prevent known transmissible infections, and no adverse effects have been reported in patients who received HD‐AM grafts . Bacteriologic test also indicated that 25 kGy γ‐irradiation achieved to complete sterilization(data not shown).…”
Section: Discussionmentioning
confidence: 94%
“…HD‐AM was also shown to reduce wound dehydration. The details of these benefits are described in clinical observations and case reports …”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…[61] Cells isolated from AM show potential to express neurosupportive factors;[62] amnion derived cells can be differentiated towards a Schwann cell-like lineage and their neurosupportive properties enhanced by the addition of neurotrophic factors. [63]…”
Section: Placental-derived Biomaterials By Medical Specialtymentioning
confidence: 99%